Evolution mechanisms of TiC ceramic particles in FeCoCrNiAl high-entropy alloy laser cladding layers. (11th September 2019) - Cai, Yangchuan; Ao, Sansan; Marwana Manladan, Sunusi; Xue, Jichao; Luo, Zhen
Abstract: FeCoCrNiAl +x(TiC) composite coatings were fabricated by laser cladding technology. Four different types of ceramic particles were observed in the cladding layers, namely, small-sized, flower-shaped, fishbone-shaped, and aggregate particles. The concentration of C element in the cladding layer, the duration of growth of the ceramic particles, and the hysteresis diffusion effect are the major factors that determine the morphology of the ceramic particles. The small-sized, flower-shaped, and fishbone-shaped particles were well bonded to the metal matrix, making crack formation difficult. On the other hand, the hard and brittle, large-sized particles were weakly bonded to the metal matrix. They broke away easily from the cladding layer during wear test to form more ploughing grooves, thereby deteriorating the wear resistance of the cladding layers.